The sulfur isotopic consequence of seawater sulfate distillation preserved in the Neoproterozoic Sete Lagoas post-glacial carbonate, eastern Brazil - Okubo, Juliana [UNESP]; Kaufman, Alan J.; Warren, Lucas [UNESP]; Evans, Michael N.; Marroquin, Selva; Varni, Michael A.; Misi, Aroldo; Bahniuk, Anelize M.; Xiao, Shuhai (Geological Soc Publ House, 2022)
Since the report of tubular structures interpreted as Cloudina from the Neoproterozoic Sete Lagoas Formation (SLF) in the Bambui basin of eastern Brazil, this stratigraphic unit has become a focus of numerous geochemical, palaeomagnetic, geochronological and sequence stratigraphic studies. Geochemical data from the SLF have been used to infer palaeoenvironmental conditions in the Bambui basin and to study the C-13 enrichment reported in this and overlying units. To further address depositional environments of the SLF, we present high-resolution delta C-13 and delta S-34 data from the SLF in the Januaria and Sete Lagoas regions. We report the presence of superheavy pyrite with delta S-34 value greater than carbonate-associated sulfate (CAS) and observe a decrease in CAS abundance coupled with a delta S-34 change from c. +20 to near +50 parts per thousand. These data are interpreted as evidence for distillation of sulfate through CAS and pyrite removal from the epeiric Bambui basin. These changes are qualitatively consistent with quantitative simulations of isotopic distillation over a period of c. 10 myr of a seawater sulfate reservoir comparable with modern concentration. Considering that Neoproterozoic seawater sulfate concentrations were probably much lower than in modern oceans, the distillation time interval was probably much shorter than 10 myr.